Study of congenital malformations among the progeny of the personnel of an interforce military shooting range in Sardinia, Italy - Satta, Giannina; Ursi, Michela; Pili, Claudia; Campagna, Marcello; Cocco, Pierluigi (La Medicina del Lavoro, 2018)
Background: Claims of an excess of congenital malformations in a village nearby the military shooting range of Salto di Quirra (PISQ), Sardinia have attracted media attention. Objective: To verify such reports with a retrospective study of the reproductive history of the PISQ personnel. Methods: In 2011, we interviewed 390 soldiers employed at the PISQ shooting range (86.7% of the total workforce) about their reproductive history, including age at first conception, number of live births and spontaneous abortions, and cases of malformations among their progeny, as well as work history and lifestyle habits. We used a job-exposure matrix to assess occupational exposure to radiofrequency, extremely low frequency electromagnetic fields, solvents and nanoparticles, and whether holding an operative job in the shooting range areas. Results: The rate of congenital malformations among the progeny of the study subjects was close to the expectation (20.2x10-3 live births, 95% CI 6.3-34.0; 8 cases observed versus 8.6 expected based on the 2005 rate of the Emilia Romagna region), it was lower in the years subsequent to the onset of service at PISQ (11.0x10-3, 95% CI 0.0-26.1; two cases observed versus 3.9 expected), and it did not vary by residence in the surrounding villages or elsewhere. None of the exposures we assessed was associated with an increase in the rate of congenital malformations. Conclusions: The limited statistical power of our study allows to exclude that a strong excess of congenital malformations occurred among the progeny of the PISQ shooting range personnel.